MON-667 Prevalence and Predictors of Diabetic Retinopathy Among Type 2 Diabetes Patients at a Tertiary Care Center - Baagar, Khaled Ahmed (J Endocr Soc, 2020)
Objective: Diabetic retinopathy (DR) is one of the most common microvascular complications of type 2 diabetes (T2D). The reported prevalence of DR from different populations in the last decade was 13 - 38.1%. A report from our center 17 years ago showed that DR prevalence was 43.6%. With the all accumulated evidence showing that diabetes control decreases DR risk and the introduction of new drugs that helped better T2D control, we aimed to assess the current prevalence and predictors of DR among patients with T2D attending out-patient department at our tertiary care center. Methods: We conducted a cross-sectional study involving 638 patients. We collected information about their baseline characteristics, confirmed DR with its severity and maculopathy diagnosis, age at T2D diagnosis, duration of T2D, and averages of HbA1C, blood pressure (BP), cholesterol, and vitamin D levels over the previous year. A statistical analysis was performed using the software SPSS 23.0. A multivariate logistic regression analysis examined the independent predictors of DR development. Results: The mean age of the patients was 55.8 ± 10.3 years, and 42.8% were males. The mean BMI was 32.4 ± 12.4 kg/m(2) with 58% had obesity. The mean duration of T2D was 11.5 ± 7.7 years, and the mean age at T2D diagnosis was 44.0 ± 9.98 years. The mean HbA1C was 8.3 ± 1.6 % with 77% had average HbA1C above 7% and 51.3% had average HbA1c above 8%. The mean systolic and diastolic BP were 136.37 ± 15.01 mmHg and 74.12 ± 8.078 mmHg, respectively. DR was diagnosed in 223 cases (35%). Of the 638 patients, 24.5% had non-proliferative DR, 9.2% had proliferative DR, and 4.2% had maculopathy. There was no significant difference in DR prevalence between males (36%) and females (34.1%) (P = 0.59). Predictors of DR development were age above 40 years, duration of T2D more than 10 years, early age of T2D diagnosis, average HbA1C more than 8%, and hypertension. Discussion: T2D is a major health challenge to our community with its very high prevalence. The prevalence of DR in T2D patients attending our institution was significant (more than one-third, 35%) in comparison to reports from other centers. However, we showed an improvement in DR development in our patients from 43.6% to 35%, probably due to better T2D and BP control. Similar to previous reports, T2D patients with older age, long T2D duration, younger age at T2D diagnosis, uncontrolled diabetes, and uncontrolled BP were more likely to develop DR. Conclusion: Physicians treating T2D patients should ensure regular retina screening especially for those with risk factors for DR. Also, they should fix the modifiable risk factors of DR; diabetes and BP control. References: (1) Alaboud et al. Saudi Med J 2016; Vol. 37 (12): 1408–1411.doi: 10.15537/smj.2016.12.17062. (2) Lim MC et al. Ann Acad Med Singapore. 2008 Sep;37(9):753–9. (3) Hammes H-P et al. PLoS ONE 10(7): e0132492. doi:10.1371/journal. pone.0132492